2014
DOI: 10.1111/josh.12206
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Breaks and Facilities in US Secondary Schools

Abstract: BACKGROUND Research on physical activity breaks and facilities (indoor and outdoor) in secondary schools is relatively limited. METHODS School administrators and students in nationally representative samples of 8th (middle school) and 10th/12th grade (high school) students were surveyed annually from 2008-09 through 2011-12. School administrators reported information about physical activity breaks and facilities. Students self-reported height, weight, and physical activity. RESULTS The prevalence of physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 32 publications
2
33
1
7
Order By: Relevance
“…Our results, consistent with those of Hood et al revealed that low‐income schools have less PAS opportunities as well as indoor and outdoor facilities. The low‐income primary schools in our sample were found to be less likely to have gymnasium, bike racks, and exterior infrastructures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results, consistent with those of Hood et al revealed that low‐income schools have less PAS opportunities as well as indoor and outdoor facilities. The low‐income primary schools in our sample were found to be less likely to have gymnasium, bike racks, and exterior infrastructures.…”
Section: Discussionsupporting
confidence: 93%
“…Schools are increasingly recognized for their potential to increase the time that children participate in MVPA in a safe and supervised setting, independent of parental availability and family financial resources . A wealth of evidence demonstrates that schools' psychosocial and physical environments associate with the amount of time students are physically active . The psychosocial environment in particular, measured by the availability of adults to supervise activities or socioeconomic indicators such as social cohesion or fragmentation, are associated with student inactivity.…”
mentioning
confidence: 99%
“…Because children and adolescents spend about half of their waking hours at school and accumulate up to 40% of their daily PA at school, the school environment has been identified as a key location for PA promotion . Much research has been done to examine the environmental correlates of PA in youth, many of which were found at the school level .…”
mentioning
confidence: 99%
“…Survey weights were appropriately scaled and applied at the student and school levels. 32,33 Consistent with previous research, 3436 we estimated separate eighth grade and tenth/12th grade models predicting the number of days that a student was physically active for at least 60 minutes. Initial diagnostic analyses indicated that the continuous count outcome did not meet linear regression assumptions; thus, Poisson regression with a logarithmic link was used.…”
Section: Methodsmentioning
confidence: 66%